1991
DOI: 10.1038/bjc.1991.484
|View full text |Cite
|
Sign up to set email alerts
|

Phase I and pharmacokinetic study of D-verapamil and doxorubicin

Abstract: Summary The calcium antagonist verapamil (a mixture of D-and L-racemers) is a potent modulator of the multi-drug resistance phenotype in vitro at a concentration of 6 gM. Clinical studies have shown dose-limiting toxicity of hypotension and heart block when plasma levels approach the concentrations active in vitro. Previous data indicate that the D-isomer is less cardioactive than the L-isomer but they appear to be equipotent in reversing drug resistance in vitro. In an attempt to increase plasma verapamil con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(21 citation statements)
references
References 14 publications
(15 reference statements)
2
19
0
Order By: Relevance
“…Plasma levels of both DVPM (2.18 ± 1.56 Lml ') and Dnorverapamil (1.57 ± 0.99 tml'1) measured at the time of epirubicin administration showed considerable interpatient variability, though values were within the range described previously for a daily dose of 1200 mg DVPM (Bisset et al, 1991). When the parent compound and active metabolite (Merry et al, 1989) levels are combined, a mean value of 3.74 Lml ' (range, 1.76 to 7.27 gml-') was achieved.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Plasma levels of both DVPM (2.18 ± 1.56 Lml ') and Dnorverapamil (1.57 ± 0.99 tml'1) measured at the time of epirubicin administration showed considerable interpatient variability, though values were within the range described previously for a daily dose of 1200 mg DVPM (Bisset et al, 1991). When the parent compound and active metabolite (Merry et al, 1989) levels are combined, a mean value of 3.74 Lml ' (range, 1.76 to 7.27 gml-') was achieved.…”
Section: Resultsmentioning
confidence: 86%
“…Whereas a large number of drugs, the prototype of which is verapamil, have now been identified which can modify the MDR phenotype in vitro, target plasma levels predicted from tissue culture data are commonly non-achievable or too toxic in vivo (Plumb et al, 1990). An atttractive alternative MDR modulating agent currently undergoing clinical investigation, is the D-isomer of the marketed drug verapamil (a racemic DL mixture), which is characterised by equal resistance reverting potential but at least 3-fold less cardiovascular activity (Bisset et al, 1991). Preliminary data of clinical trials involving D-verapamil (DVPM) in the treatment of colorectal (Kornek et al, 1992) and pancreatic cancer (unpublished data) suggest a possible enhancement of anthracycline-related myelotoxicity.…”
mentioning
confidence: 99%
“…In clinical trials promising results have been observed in patients with multiple myeloma, lymphoma and leukemia (Dalton et al 1989;Solary et al 1992;Sonneveld et al 1992;List et al 1993). In studies with solid tumours chemosensitizers showed less efficacy with responses in a minority of the patients only (Miller et al 1988;Bissett et al 1991;Philip et al 1992;Verweij et al 1991). Besides, some authors have reported on enhancement of toxic side-effects, like myelosuppression, by the addition of chemosensitizers to the therapeutic regimen (Fiqueredo et al 1990;Verweij et al 1991; Yahanda et al 1992).…”
Section: Introductionmentioning
confidence: 91%
“…These studies (Bissett et al, 1991;Scheithauer et al, 1993) suggest that, while D-verapamil is less cardiotoxic than the racemic mixture, a significant number of patients develop cardiovascular side-effects until the dose is dropped to 800mgday-' or less (resulting in a serum level of about 1000 ytg 1-1).…”
Section: Discussionmentioning
confidence: 99%
“…Verapamil is normally given as a raecemic mixture of the L-isomer, which is 10-fold more effective as a calcium channel blocker and hence more cardiotoxic, and the D-isomer, which is as effective at reversing MDR in preclinical models (Bissett et al, 1991;Scheithauer et al, 1993).…”
mentioning
confidence: 99%